Research Library's Role and Place in the Educational Environment of Pedagogical University - E. O. Frantcuzskaia; N. A. Semenenko; N. A. Medova; E. A. Gordeyeva (Высшее образование в России)
The paper provides some results of the library reader survey which allowed establishing the new role and place of the research library of a pedagogical university. The creative role of the research library determines the possible options of interaction between the library and scientific and educational departments of the pedagogical university. In the educational environment, the library becomes a “third place” between home and classroom.